Plasma citrulline concentration, a marker for intestinal functionality, reflects exercise intensity in healthy young men. Issue 5 (October 2019) - Kartaram, Shirley; Mensink, Marco; Teunis, Marc; Schoen, Eric; Witte, Gerrit; Janssen Duijghuijsen, Lonneke; Verschuren, Martie; Mohrmann, Karin; M'Rabet, Laura; Knipping, Karen; Wittink, Harriet; van Helvoort, Ardy; et al.
Summary: Background & aims: Plasma citrulline concentration is considered to be a marker for enterocyte metabolic mass and to reflect its reduction as may occur during intestinal dysfunction. Strenuous exercise can act as a stressor to induce small intestinal injury. Our previous studies suggest that this comprises the intestinal ability to produce citrulline from a glutamine-rich protein bolus. In this study we investigated the effects of different exercise intensities and hydration state on citrulline and iFABP levels following a post-exercise glutamine bolus in healthy young men. Methods: Fifteen healthy young men (20–35 yrs, VO2 max 56.9 ± 3.9 ml kg −1  min −1 ) performed in a randomly assigned cross-over design, a rest (protocol 1) and four cycle ergometer protocols. The volunteers cycled submaximal at different percentages of their individual pre-assessed maximum workload (Wmax): 70% Wmax in hydrated (protocol 2) and dehydrated state (protocol 3), 50% Wmax (protocol 4) and intermittent 85/55% Wmax in blocks of 2 min (protocol 5). Immediately after 1 h exercise or rest, subjects were given a glutamine bolus with added alanine as an iso-caloric internal standard (7.5 g of each amino acid). Blood samples were collected before, during and after rest or exercise, up to 24 h post onset of the experiment. Amino acids and urea were analysed as metabolic markers, creatine phosphokinase and iFABP as markers of muscle and intestinal damage, respectively. Data were analysed using a multilevel mixed linear statistical model. p values were corrected for multiple testing. Results: Citrulline levels already increased before glutamine supplementation during normal hydrated exercise, while this was not observed in the dehydrated and rest protocols. The low intensity exercise protocol (50% Wmax) showed the highest increase in citrulline levels both during exercise (43.83 μmol/L ± 2.63 (p < 0.001)) and after glutamine consumption (50.54 μmol/L ± 2.62) compared to the rest protocol (28.97 μmol/L ± 1.503 and 41.65 μmol/L ± 1.96, respectively, p < 0.05). However, following strenuous exercise at 70% Wmax in the dehydrated state, citrulline levels did not increase during exercise and less after the glutamine consumption when compared to the resting condition and hydrated protocols. In line with this, serum iFABP levels were the highest with the strenuous dehydrated protocol (1443.72 μmol/L ± 249.9, p < 0.001), followed by the high intensity exercise at 70% Wmax in the hydrated condition. Conclusions: Exercise induces an increase in plasma citrulline, irrespective of a glutamine bolus. The extent to which this occurs is dependent on exercise intensity and the hydration state of the subjects. The same holds true for both the post-exercise increase in citrulline levels following glutamine supplementation and serum iFABP levels. These data indicate that citrulline release during exercise and after an oral glutamine bolus might be dependent on the intestinal health state and therefore on intestinal functionality. Glutamine is known to play a major role in intestinal physiology and the maintenance of gut health and barrier function. Together, this suggests that in clinical practice, a glutamine bolus to increase citrulline levels after exercise might be preferable compared to supplementing citrulline itself. To our knowledge this is the first time that exercise workload-related effects on plasma citrulline are reported in relation to intestinal damage.